2021
DOI: 10.1111/ger.12577
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and gap analysis of frailty and oral health characteristics in older adults: A call for clinical translation

Abstract: Objective: This systematic review updates the evidence for association between oral health characteristics and frailty status, identifying gaps in translational dental research and application of frailty assessment into clinical practice. Background:Clinicians have little guidance on stage-appropriate dental treatment for medically complex older adults. Oral health characteristics have been associated with frailty status, determined through validated assessment tools representing a concise measure of health. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Twenty-three systematic reviews provided data on physical outcomes, of which 7 included a meta-analysis. Nine systematic reviews (2 with a meta-analysis) ( 29 , 30 ) focused on respiratory diseases ( 13 , 15 , 50 56 ), 5 (2 with a meta-analysis) ( 39 , 40 ) on age-related oral changes ( 39 43 ), 6 (3 with a meta-analysis) ( 28 , 36 , 38 ) mainly on malnutrition and 3 (none with a meta-analysis) on frailty ( 29 , 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three systematic reviews provided data on physical outcomes, of which 7 included a meta-analysis. Nine systematic reviews (2 with a meta-analysis) ( 29 , 30 ) focused on respiratory diseases ( 13 , 15 , 50 56 ), 5 (2 with a meta-analysis) ( 39 , 40 ) on age-related oral changes ( 39 43 ), 6 (3 with a meta-analysis) ( 28 , 36 , 38 ) mainly on malnutrition and 3 (none with a meta-analysis) on frailty ( 29 , 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is an increasing amount of research and systematic reviews on the impacts of oral health on different health outcomes, and published articles on corresponding topics have covered a variety of general health outcomes among elderly individuals, such studies have mainly focused on the association between oral health and some specific diseases; a body of work describing the current landscape of intervention and nursing measures that links oral health and the diverse outcomes covering physical, mental, and social health is still missing ( 28 , 29 ). Accordingly, it is still challenging for practitioners and decision-makers to find, interpret, and utilize related evidence in daily nursing and medical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that focusing on frailty and pre-frailty is important for preventing nursing care and concluded that exercise and nutrition interventions are among the most successful methods to reduce frailty [ 7 , 8 ]. However, these reviews did not focus on oral functions, although oral functions are closely related to physical functions [ 9 , 10 ] and nutrition [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on association between masticatory dysfunction and frailty in the literature is mixed: some studies have documented significant associations [16], but others did not [17,18]. Although several review papers have investigated frailty and oral health indicators, including masticatory dysfunction [16,[19][20][21], none of them specifically focused on masticatory dysfunction or conducted a meta-analysis. Therefore, the objectives of this study are to perform a systematic literature review specifically on the association between self-reported masticatory dysfunction and frailty among community-dwelling older adults, and to synthesize pooled quantitative evidence by conducting a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%